2016
DOI: 10.1371/journal.pone.0156017
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Proteomic Analysis of A549 Cells Infected with Avian Influenza Virus H7N9 and Influenza A Virus H1N1

Abstract: A newly emerged H7N9 influenza virus poses high risk to human beings. However, the pathogenic mechanism of the virus remains unclear. The temporal response of primary human alveolar adenocarcinoma epithelial cells (A549) infected with H7N9 influenza virus and H1N1 influenza A virus (H1N1, pdm09) were evaluated using the proteomics approaches (2D-DIGE combined with MALDI-TOF-MS/MS) at 24, 48 and 72 hours post of the infection (hpi). There were 11, 12 and 33 proteins with significant different expressions (P<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The airway primary cells we used were non-transformed cells and can mimic the normal physiological environment. To represent respiratory cells from human origin, we used human lung epithelial cell line A549, which is yet another cell line used for influenza studies [ 64 , 65 ]. The increase in the viral titer demonstrated in the MDCK cells by 2 logs, at a lower MOI of 0.01, could be due to the adaptation of this EIV isolate to grow in MDCK cells, as the virus was initially isolated in MDCK cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The airway primary cells we used were non-transformed cells and can mimic the normal physiological environment. To represent respiratory cells from human origin, we used human lung epithelial cell line A549, which is yet another cell line used for influenza studies [ 64 , 65 ]. The increase in the viral titer demonstrated in the MDCK cells by 2 logs, at a lower MOI of 0.01, could be due to the adaptation of this EIV isolate to grow in MDCK cells, as the virus was initially isolated in MDCK cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there was no other research on the plasma proteomic changes of H7N9 patients yet, but there were several researches on the differentially expressed proteins using infected human cells with H7N9 virus. [ 17 18 ] Ding et al . have analyzed the differentially expressed proteins in A549 cells infected with H7N9 virus at 24, 48, and 72 h pi and also performed network analysis of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…As the researchers focused on the differentially expressed proteins at each postinfection time point separately, their results were inconsistent with our findings which analyzed the proteins with time-related trend after H7N9 infection. [ 17 ] Furthermore, using the plasma samples from the H7N9 patient, our results might get more insight into the development the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Using multiplex iTRAQ labelled quantification, they found that NRF2 was associated with infection 78 with HPAI strains of influenza [10]. Ding et al(2016) carried out similar research work in A549 79 infected with pdmH1N1 and H7N9 by labelling digested proteins with Cy-dye followed by 80 identification using MALDI-TOF-MS/MS, and found that down-regulation of CAPZA1, OAT, 81 PCBP1, EIF5A were related to the death of cells infected with H7N9, and down-regulation of 82 PAFAH1B2 was related to the later clinical symptoms in patients infected with H7N9 [11]. 83 Sadewasser et al(2017) performed SILAC labelled proteomic assays on human HEK 293T and A549, 84 characterized sets of cellular factors alternatively regulated in cells infected with H3 or H7 AIVs, and 85 suggested that VPRBP(DCAF1) was identified as a novel drug target [12].…”
Section: Introduction 64mentioning
confidence: 99%